2011
DOI: 10.1111/j.1939-0025.2010.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Burden of caregivers of patients with bipolar affective disorders.

Abstract: Thirty-two problem-oriented interviews with caregivers of patients with bipolar affective disorders were analyzed using content analysis. The 722 statements of caregivers about their experiences of subjective burden because of the illness of their family members were summarized in 49 global statements and correlated by factor analysis to 10 types of burden. In particular, patients' noncompliance as well as the helplessness of the caregivers in interaction with the (changing) depressive and manic symptoms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 41 publications
2
32
1
10
Order By: Relevance
“…Similar findings have been reported by a number of studies. Rita Bauer et al [20] found that manic symptoms of the ill family members emerged as serious burdens on the caregivers. Findings from Eduard Vieta et al [21] revealed that up to 93% of caregivers of bipolar patients suffered from a moderate or higher level of stress when the patient was admitted to an inpatient unit or outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported by a number of studies. Rita Bauer et al [20] found that manic symptoms of the ill family members emerged as serious burdens on the caregivers. Findings from Eduard Vieta et al [21] revealed that up to 93% of caregivers of bipolar patients suffered from a moderate or higher level of stress when the patient was admitted to an inpatient unit or outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%
“…www.kan.or.kr 들은 가족의 성격성향 [9,10], 가족이 인지하는 질병의 심각성 [1,11,12], 질병 불확실성 [13,14], 사회적 지지 [5,[15][16][17] 및 돌봄효능감 [18][19][20][21] 등이 다. 질병의 심각성 [11]이나 질병에 대한 불확실성 [14] …”
unclassified
“…Of 14 articles that addressed caregiver burden related to mania or hypomania, eight reported an effect on caregivers' social relationships (Beentjes et al, 2012). Content analysis of interviews with caregivers revealed that a majority experienced suspended social contacts, rejection, and loneliness because of the patient's bipolar illness (Bauer et al, 2011). Another qualitative study reported about spouses lacking support and describing themselves as "alone together" with their BD partners (van der Voort et al, 2009).…”
Section: Discussionmentioning
confidence: 98%